Small Molecule Screen Reveals Joint Regulation of Stress Granule Formation and Lipid Droplet Biogenesis - Amen, Triana; Kaganovich, Daniel (Frontiers in Cell and Developmental Biology, 2021)
Metabolic regulation is a necessary component of all stress response pathways, because all different mechanisms of stress-adaptation place high energy demands on the cell. Mechanisms that integrate diverse stress response pathways with their metabolic components are therefore of great interest, but few are known. We show that Stress Granule (SG) formation, a common adaptive response to a variety of stresses, is reciprocally regulated by the pathways inducing Lipid Droplet accumulation. Inability to upregulate lipid droplets reduces Stress Granule formation. Stress Granule formation in turn drives Lipid Droplet clustering and fatty acid accumulation. Our findings reveal a novel connection between stress response pathways and new modifiers of Stress Granule formation.